MO422: Strong Positive Association Between GFR and the Urine-To-Plasma Urea Concentration Ratio in Patients With Sickle Cell Disease. Possible Functional Meaning. (3rd May 2022) - Bankir, Lise; Lionnet, François; Saint Jacques, Camille; Santin, Aline; Chieze, Rémi; Frochot, Vincent; Letavernier, Emmanuel; Haymann, Jean-Philippe
Abstract: BACKGROUND AND AIMS: Sickle cell disease (SCD) induces a decline in urine concentration and progressive deterioration of kidney (K) function. Hyperfiltration is often observed before this decline, and plasma urea is low. Oral urea or hydroxyurea improves the condition of these patients (pts). These observations draw the attention to renal urea handling in SCD. Studies suggest that addition of urea into the loop of Henle may indirectly modify NaCl concentration at the macula densa and induce a rise in glomerular filtration rate (GFR) by depressing the tubule-glomerular feedback (TGF) [1 ]. The urine-to-plasma urea concentration ratio (U/P urea) is a novel marker associated with GFR and the progression of disease in ADPKD [2 ]. The present study addresses the relationship of U/P urea with GFR in SCD pts. METHOD: A total of 184 homozygous SCD pts referred to our department were included. They underwent extensive evaluation including measured GFR (mGFR) ( 51 Cr EDTA clearance) and plasma and 24-h urine chemistries. The association between mGFR and U/P urea was tested using univariate, and multivariate stepwise regression analyses. RESULTS: Mean age was 35.6 ± 2.8 years (mean ± SD) and body mass index (BMI) 22.2 ± 0.3 kg/m 2 . Mean mGFR was 107 ± 3 ml/min x 1.73m 2 . Hyperfiltration was observed in 37% of pts. Urine volume (UV) 1.71 ± 0.75 L/24h. Urea excretion 267 ± 151 mmol/24h. In 13% of pts fractional excretion of urea (FEurea ) exceeded 50%. U/P urea (42 ± 20) varied from 6 to 112. It was not associated with 24-h urea excretion but showed a negative association with UV (P < 0.007). mGFR was strongly and positively associated with U/P urea ( r = 0.58, P < 0.0001) but not with U/P osmolarity (see Figure and Table ). mGFR was also associated with U/P creatinine although more weakly (r = 0.266, p < 0.0001) and with BMI and negatively associated with age, MAP and serum creatinine (creat). After adjustment for U/P creat, the association between mGFR and U/P urea remained highly significant, whereas, after adjustment for U/P urea, the association between mGFR and U/P creat disappeared. In multivariate regression, mGFR remained strongly associated with U/P urea. CONCLUSION: Our data show a strong association between mGFR and U/P urea that remains highly significant after multivariate analysis. i) This suggests that a specific estimated GFR equation for SCD patients including the U/P urea ratio could be clinically more relevant than CKD-EPI equations. ii) A specific mechanism may link GFR and intrarenal urea handling, as U/P urea but not U/P osmolarity appears to be involved. Urea could play a role, indirectly, in the regulation of GFR [1 ]. In SCD, the longer transit time of the blood in vasa recta may favour countercurrent exchanges and lead to a greater addition of urea in loops of Henle (increasing the U/P urea ratio) and thus increasing GFR by reducing TGF. Sickled red cells and resulting in slower blood flow in the medulla may selectively influence urea handling, participating in high FEurea and GFR often observed in SCD pts. iii) As is the case in ADPKD, more attention should be given to longitudinal studies to the relationship between U/P urea and kidney disease progression in SCD pts.